Computational Evaluation of Methyl \(α\)-D-Glucopyranoside Derivatives as Antibacterial Agents Targeting Bacillus subtilis HmoB - Sarkar M. A. Kawsar; Md. Ahad Hossain (Recent Developments in Chemistry and Biochemistry Research Vol. 5, 2024)
Carbohydrates are the most abundant macromolecules among the organic substances present in living organisms on Earth. Monosaccharide derivatives are essential in biological chemistry because of their ability to inhibit bacterial infections and produce physiologically active molecules. Designing innovative antibacterial medicines with new structural scaffolds to treat drug-resistant microorganisms is a pressing issue. This study aimed to determine the binding affinity of previously synthesized methyl \(α\)-D-glucopyranoside (MDGP) derivatives by molecular docking and molecular dynamics, as well as their physicochemical and pharmacokinetic features. B3LYP/3-21G was utilized to perform density functional theory (DFT) calculations on the MDGP derivatives and to determine the partial atomic charge and molecular electrostatic potential (MEP). The antibacterial effects of the proposed derivatives were assessed using AutoDock’s molecular docking investigation with Bacillus subtilis HmoB haem oxygenase. The binding affinity according to the molecular docking score for Derivatives 8-10 (-10.11, -10.41, and -12.20 kcal/mol) against the bacterial pathogen B. subtilis HmoB indicates that these derivatives are potential antibacterial agents. Furthermore, a 100-ns molecular dynamics simulation confirmed the stable conformation and binding behavior of the MDGP derivatives in a stimulating environment. Furthermore, in an in silico ADMET analysis, the toxicity and bioactivity characteristics of MDGP and its derivatives were estimated to evaluate their safe uses and anticipate the need for further study of clinical phases as therapeutic molecules utilizing software and an online database. Our proposed novel MDGP derivatives may demonstrate first-rate and superior pharmacological properties in medicinal chemistry, providing valuable information for future studies on their biological activity. This research may reveal the chemical, thermal, biological, and pharmacokinetic properties of MDGP derivatives.